1995
DOI: 10.1007/bf00187182
|View full text |Cite
|
Sign up to set email alerts
|

Early development and organization of the retinopetal system in the larval sea lamprey, Petromyzon marinus L.

Abstract: Development of the retinopetal system of the larval sea lamprey, Petromyzon marinus, was investigated following labelling of this system by injection of horseradish peroxidase into the orbit. This study extends our previous report on larval stages and provides a detailed description of the development of this system. We present quantitative and qualitative evidence suggesting that the retinopetal nuclei of Schober's M2-M5 nucleus, the mesencephalic reticular area and the tectum arise sequentially in that order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 40 publications
(46 reference statements)
4
22
1
Order By: Relevance
“…For example, previous tract-tracing studies of the oculomotor and retinopetal nuclei of the sea lamprey have shown that the number of retrogradely labeled neurons in these systems increases markedly throughout the larval period (Pombal et al, 1994;Rodicio et al, 1995), which is consistent with the continued presence of PCNA-ir cells in ventricular regions adjacent to these nuclei (present results). However, for most brain regions there are no data on the growth of neuronal populations.…”
Section: Late-proliferating Regionssupporting
confidence: 88%
“…For example, previous tract-tracing studies of the oculomotor and retinopetal nuclei of the sea lamprey have shown that the number of retrogradely labeled neurons in these systems increases markedly throughout the larval period (Pombal et al, 1994;Rodicio et al, 1995), which is consistent with the continued presence of PCNA-ir cells in ventricular regions adjacent to these nuclei (present results). However, for most brain regions there are no data on the growth of neuronal populations.…”
Section: Late-proliferating Regionssupporting
confidence: 88%
“…Following application of biocytin in the eye bulb, both retinofugal and retinopetal connections were revealed, as previously reported by using other techniques [Kennedy and Rubinson, 1977;Kosareva, 1980;Repérant et al, 1980Repérant et al, , 1982Vesselkin et al, 1980Vesselkin et al, , 1984Vesselkin et al, , 1996Vesselkin and Repérant, 1985;De Miguel et al, 1990;Rodicio et al, 1995]. Briefly, retinofugal fibers of the optic tract projected mostly to the superficial layers of the contralateral OT (SM and SO) and constituted the lateral and axial optic tracts, whereas the retinopetal cells distributed in the M5 nucleus of Schöber and the mesencephalic reticular area ( fig.…”
Section: Complementary Experimentssupporting
confidence: 49%
“…Some large dorsal dendrites coursed in the OT, where some cell bodies could also be observed. The M5 nucleus of Schöber and the mesencephalic reticular area are two well-known retinopetal nuclei in lampreys [Kosareva, 1980;Repérant et al, 1980Repérant et al, , 1982Vesselkin et al, 1980Vesselkin et al, , 1984Vesselkin et al, , 1996Vesselkin and Repérant, 1985;Rodicio et al, 1995]. These studies showed that the retinopetal cells send their axons rostrally through the axial optic tract on the way to the retina and have long dendrites that can reach the OT.…”
Section: Afferent Connections Of the Adult Lamprey Otmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies with tract-tracing methods for the sea lamprey have suggested that this system appears later than was in fact observed here, given the absence or rarity of labeled M5 neurons after horseradish peroxidase application to the eye in larvae between 11 and 20 mm in length (Rodicio et al, 1995). The present immunocytochemical results revealed the presence of GABAergic centrifugal fibers in prolarval eyes, which is earlier than previously thought and only a few days latter than the start of differentiation of the first photoreceptors.…”
Section: Development Of Gabaergic Structures In the Retina And Pinealcontrasting
confidence: 46%